Crystal structure and Hirshfeld analysis of the kryptoracemate: bis(mefloquinium) chloride p-fluorobenzenesulphonate - Jotani, Mukesh M.; Wardell, James L.; Tiekink, Edward R. T. * (De Gruyter, 2016)
The crystal structure analysis of the bis(mefloquinium) chloride p-fluorobenzenesulphonate salt reveals a rare example of a kryptoracemate given that the cations exhibit a non-crystallographic enantiomeric relationship. The conformations of the cations are based on a skewed letter L with the (piperidinium-2-yl)methanol group sitting almost normal to and directed away from the quinolinyl residue. The most prominent feature of the molecular packing is the formation of supramolecular helical chains along the a-axis, being sustained by pairs of hydroxyl-O–H···O (sulphonate), piperidinium-N–H···O (sulphonate) and piperidinium-N–H···Cl hydrogen bonds. Geometric and Hirshfeld surface analyses of the crystal structure shows significant differences in supramolecular aggregation between the cations due to the presence of different anions and this is the likely reason for the observed kryptoracemic behaviour.